Expansion, speciation and a change of trophic niche: a case study of the Early Pleistocene ground squirrels Spermophilus polonicus and S. praecox. (2nd January 2021) - Popova, Lilia; Lemanik, Anna; Ulbricht, Arlett; Nadachowski, Adam
ABSTRACT: During the Early Pleistocene, two ground squirrel species, Spermophilus praecox (northern Black Sea area) and S. polonicus (Central Europe) coexisted in geographically well-separated ranges. Studied samples from Tiligul (Ukraine) and Kamyk (Poland) have approximately the same biostratigraphical age: the early Odessa faunal complex (Tiligul) and the Villanyian-Biharian transition (Kamyk). A significant difference in trophic niches and a high similarity of phylogenetically significant tooth characters have been established for S. praecox and S. polonicus . Seemingly archaic features of S. polonicus are identified as adaptations to a predominance of non-abrasive parts of plants in the diet, while phylogenetically significant characters are either close to those of S. praecox (e.g. patterns of bunodonty) or more advanced (e.g. the relationship between the height of cingula and main lophs). The diet of S. praecox included a higher amount of the abrasive food and underground parts of plants. The effects of this abrasive diet are seen in the early flattening of occlusal surfaces. We suggest that S. polonicus branched off from early S. praecox between 2.5 and 2.0 Ma; the speciation was triggered by an expansion to the northwest, probably, along the Dniester valley.